Magnetic Resonance Imaging of Multiple Sclerosis: A Study of Pulse-Technique Efficacy - Runge, Val M.; Price, Ann C.; Kirshner, Howard S.; Allen, Joseph H.; Partain, C. Leon; James, A. Everette (American Journal of Neuroradiology, 1984)
Forty-two patients with the clinical diagnosis of multiple sclerosis were examined by proton magnetic resonance imaging (MRI) at 0.5 T. An extensive protocol was used to facilitate a comparison of the efficacy of different pulse techniques. Results were also compared in 39 cases with high-resolution x-ray computed tomography (CT). MRI revealed characteristic abnormalities in each case, whereas CT was positive in only 15 of 33 patients. Milder grades 1 and 2 disease were usually undetected by CT, and in all cases, the abnormalities noted on MRI were much more extensive than on CT. Cerebral abnormalities were best shown with the T2-weighted spin-echo sequence (TE/TR = 120/1000); brainstem lesions were best defined on the inversion-recovery sequence (TE/TI/TR = 30/400/1250). Increasing TE to 120 msec and TR to 2000 msec heightened the contrast between normal and abnormal white matter. However, the signal intensity of cerebrospinal fluid with this pulse technique obscured some abnormalities.